2020
DOI: 10.1002/anie.202005443
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Dehalogenation in On‐Surface Aryl–Aryl Coupling

Abstract: In the emerging field of on‐surface synthesis, dehalogenative aryl–aryl coupling is unarguably the most prominent tool for the fabrication of covalently bonded carbon‐based nanomaterials. Despite its importance, the reaction kinetics are still poorly understood. Here we present a comprehensive temperature‐programmed x‐ray photoelectron spectroscopy investigation of reaction kinetics and energetics in the prototypical on‐surface dehalogenative polymerization of 4,4′′‐dibromo‐p‐terphenyl into poly(para‐phenylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Interestingly, the onset temperatures for the debromination process on PdGa{111} correspond well to those reported for Cu(111). [20,44] This observation supports the presumption that these surfaces have a comparable catalytic activity due to the similar average energy of d-band electrons (d-band center). [27,45,46] An intriguing difference is that on PdGa{111} surfaces the BMA debromination occurs over a wider temperature range than on Cu(111).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, the onset temperatures for the debromination process on PdGa{111} correspond well to those reported for Cu(111). [20,44] This observation supports the presumption that these surfaces have a comparable catalytic activity due to the similar average energy of d-band electrons (d-band center). [27,45,46] An intriguing difference is that on PdGa{111} surfaces the BMA debromination occurs over a wider temperature range than on Cu(111).…”
supporting
confidence: 79%
“…While TPD is an established method to determine enantiospecific reaction kinetics, [ 5,15 ] applications of TP‐XPS have been limited to symmetric reactions so far. [ 16–20 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On-surface synthesis has received great attention as a method to create atomically-precise one-dimensional (1D) and two-dimensional (2D) polymers with intriguing properties [1][2][3][4][5][6][7][8]. In particular, graphene nanoribbons (GNRs), a category of quasi-1D nanomaterials derived from graphene, have been widely studied due to their tuneable electronic properties and potential applications in semiconductor de-vices, such as field-effect transistors and spintronics [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…So far, few studies have focused on GNR synthesis on Cu(111) due to the stronger surface interaction, despite the lower temperature for dehalogenation [23,24,26,27]. It has been shown that chiral GNRs can be synthesized on Cu(111) [24] using the same precursor that yields non-chiral 7-AGNR on Au(111) [1] and that dehalogenation can be reversible on Au(111) but not Cu(111) [7], which implies that the reaction pathway and products achieved could be controlled through the choice of substrate.…”
Section: Introductionmentioning
confidence: 99%